PENGARUH DANA PIHAK KETIGA, CAPITAL ADEQUACY RATIO, DAN NON PERFORMING LOAN TERHADAP PENYALURAN KREDIT PERBANKAN PADA PT. BANK RAKYAT INDONESIA (PERSERO), TBK. PERIODE 2011-2015 - Akromul Ibad (Jurnal Ekonomi Perusahaan, 2017)
This study aims to determine the effect of DPK, CAR and NPL on bank lending at PT. Bank Rakyat Indonesia (Persero), Tbk. The data used is quarterly for 5 (five) years from 2011 to 2015 which is gathered from published financial statements collected by documentation techniques through the website www.bri.co.id. The independent variables of this study are Third Party Funds (TPF), Capital Adequacy Ratio (CAR) and Non Performing Loans (NPL). The data analysis technique used is multiple linear regression which is preceded by testing the classic assumption test, then regression analysis and model test consisting of coefficient of determination analysis, simultaneous test (F test) and partial test (t test) using SPSS program assistance 19.0. The results of the examination is that Third Party Funds (TPF) have a positive and significant effect on lending PT. Bank Rakyat Indonesia (Persero), Tbk, Capital Adequacy Ratio (CAR) has a positive and significant effect on lending PT. Bank Rakyat Indonesia (Persero), Tbk and Non Performing Loans (NPL) have a positive and insignificant effect on lending PT. Bank Rakyat Indonesia (Persero), Tbk.Keywords: Bank Lending, Third Party Funds, Capital Adequacy Ratio, Non - Performing Loans, Classic assumption and Multiple regression